(untitled) - Salam, Abdus (Singapore, 1994)
This is a selection from over 250 papers published by Abdus Salam. Professor Salam has been Professor of Theoretical Physics at Imperial College, London and Director of the International Centre for Theoretical Physics in Trieste, for which he was largely responsible for creating. He is one of the most distinguished theoretical physicists of his generation and won the Nobel Prize for Physics in 1979 for his work on the unification of electromagnetic and weak interactions.
Keywords: Electroweak interactions,Hạt (vật lý hạt nhân),Tương tác điện yếu,Particles (Nuclear physics)